Early Onset Delinquency and Violent Delinquency in Adolescence: the Role of Abusive Parents and Delinquent Peer Associations - Kim, Jihoon (Crime & delinquency, 2023)
Early onset delinquency is a risk factor for offending over the life-course. This study aims to identify factors that modify the link between early onset of delinquency and later violence. Results show that engaging delinquency earlier, associating with deviant friends, and experiencing parental abuse have independent impacts on increased risk of violence. Also, early onset has positive interactions with peer delinquency and parental abuse. These findings enhance our understanding of the mechanisms through which early onset of delinquency is related to later violence and imply the importance of family- and school-based early interventions. Findings also highlight the importance of considering interactions between early onset delinquency and social risk factors in refining theories used to explain violence throughout the life course.